Perancangan Arsitektur, Pembangunan Web-GIS, dan Analisis Kesesuaian Lahan Pertanian Tanaman Padi Menggunakan Metode GIS-MCDA di Kota Batu - Amaliah Khoirun Nisyak; Fatwa Ramdani; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Agriculture still plays an important role in the economy in the Batu City. In addition to horticultural plants, the Batu City is also a producer of rice plant though not many areas planted with rice. According to the results of the interviews from the Department of Agriculture and Forestry of Batu City, within one year, the land planted with rice only once or twice that should be done 3 times. It is because the farmers do not know the land is actually appropriate or not for rice plant. Department of Agriculture and Forestry of Batu City currently does not yet have data related to whether the land is actually appropriate or not for planting rice. The data is required, so it can be used as a reference in managing agricultural land. To get the results of the land suitability, this study will apply the methods of GIS-MCDA (Multi Criteria Decision Analysis), which used the 9 criterias that affect the suitability of the land and the results will be applied in Geographic Information Systems (GIS) based on the web. GIS based on the web (Web-GIS) is built according to the architectural design. Web-GIS architecture consists of 3 layers, i.e. the Client Layer, Service Layer, and Layer Support. Based on the results of land suitability analysis, this research get 4 results of land suitability class i.e., S1, S2, S3, and NS. Total area of suitability class S1 is 739.42 ha with percentage 3.7%, total area of suitability class S2 is 7375.91 ha with percentage 37%, total area of suitability class S3 is 3706.20 ha with percentage 18.6%, and total area of suitability class NS is 8120.02 ha with percentage 40.7%.